One-Stage Implant-Retaining Revision for Simultaneous Bilateral Infected Total Knee Arthroplasty: A Report of a Rare Case - Nils Wirries; Lars-René Tuecking; Michael Skutek (Case Reports in Orthopedics)
There is little information on the management of simultaneous infected total knee arthroplasties in the same patient. Although general principles of management for periprosthetic joint infection apply, there might be certain aspects worth to be considered. We present a case of a 78-year-old patient, who was referred in preseptic conditions 10 years following bilateral TKA. The onset of symptoms was less than one week, proposing an acute hematogenous infection. Analysis of joint fluid revealed that both of his TKAs were infected with Streptococcus sanguinis. Diagnostic algorithms, surgical principles, and the course of the patients following bilateral revision are being described. The reasons for an implant-retaining procedure with irrigation and debridement including the exchange of the polyethylene liners are being discussed as well as possible principles of management of bilateral periprosthetic joint infections.